Две судьбы-2: [романы] / Семен Малков - Малков Семен Наумович (Гелиос, 2003)
Экземпляры: АБ (20180301) / Инвентарный номер: 40686 / Цена: 92.60 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 19 / ББК: 84(2Рос=Рус)6